Transformations of the body from traditional expression to subjectivity : Marina Abramivic as a model. (Al-Academy, 2022)
The way artists deal with body in their artistic works has had so many forms and methods, whether as an object for their drawings or as a material to create live artistic performances that relate to the idea of correspondence and interaction between different artistic categories such as: drama, dance, and painting as it is the case of the artist Marina Abramovic who has always used her body as an artistic unit to generate meaning and to perform her lively shows.To go deeper into her career, our work was divided into 3 sections:The first section was devoted to follow the main artistic stages that her body had gone through, starting with paintings she performed using concepts based on acting, simulation and nudity and ending with presenting the body as a material presenting the painting act.The second section was dedicated to the interpretation of some of her works, Marina who is no longer focusing on the sacred side of the body, broke all the previous widespread asthetic standards.To shed light on her works, we explored in the third section the interactive relationship between Maria Abramovic and the viewer who has become a real active element in her artistic performances instead of being a mere spectator.We then concluded by referring to the concept of the body which has moved from its narrow limits to more open modern expressive practices that are based on the unity and the interaction of all genres of arts among them